2010
DOI: 10.3174/ajnr.a2195
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Microstructure Changes in the Thalamus in Parkinson Disease with Depression: A Diffusion Tensor MR Imaging Study

Abstract: BACKGROUND AND PURPOSE:Depression occurs frequently in PD; however the neural basis of depression in PD remains unclear. The aim of this study was to characterize possible depressionrelated white matter microstructural changes in the thalamus of patients with DPD compared with those with NDPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 42 publications
6
73
2
3
Order By: Relevance
“…Of the 38 studies on depression, 33 reported findings from one single imaging modality: 19 used either PET [11, 12, 13,15, 16, 17, 18, 19] or SPECT 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 techniques, four used T1‐weighted imaging 31, 32, 33, three used DTI 34, 35, 36, six used resting state functional MRI (RS‐FMRI) 37, 38, 39, 40, 41, 42 and two used TCS methods 43, 44. The remaining four of the 38 studies reported findings from structural T1‐weighted imaging plus another imaging method, including PET 14, DTI 45, task FMRI 46 and RS‐FMRI 47, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 38 studies on depression, 33 reported findings from one single imaging modality: 19 used either PET [11, 12, 13,15, 16, 17, 18, 19] or SPECT 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 techniques, four used T1‐weighted imaging 31, 32, 33, three used DTI 34, 35, 36, six used resting state functional MRI (RS‐FMRI) 37, 38, 39, 40, 41, 42 and two used TCS methods 43, 44. The remaining four of the 38 studies reported findings from structural T1‐weighted imaging plus another imaging method, including PET 14, DTI 45, task FMRI 46 and RS‐FMRI 47, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The other two studies applying TCS demonstrated hypoechogenicity in the brainstem raphe in dPD patients as opposed to HCs and non‐depressed PD patients 43, 48. Using DTI techniques, three out of four studies reported compromised white matter connectivity indexed by decreased fractional anisotropy (FA) in various tracts, including the bilateral anterior cingulate cortex and thalamus and multiple tracts connecting to the left frontal and deep temporal lobes 34, 35, 36. However, one study reported a non‐significant group difference in the FA of the corpus callosum and uncinate fasciculus, a tract that interconnects the amygdala, hippocampus, temporal pole and the orbitofrontal cortex 45.…”
Section: Methodsmentioning
confidence: 99%
“…These studies revealed that PD patients with depression had white matter reductions in the right anterior cingulate bundle, inferior orbitofrontal regions and in the left inferior parietal lobe [94], the frontal lobe bilaterally, possibly representing dysfunction in bilateral anterior cingulate bundles [96], and the mediodorsal nucleus of the thalamus bilaterally [95].…”
Section: Depressionmentioning
confidence: 96%
“…We found 11 imaging studies that have explored the neural bases of PD patients with and without depression using different imaging techniques [91][92][93][94][95][96][97][98][99][100][101] (See table 4). Among these studies, there is only one study that found no differences in brain regions between PD patients with and without depression [97] (In this study patients had mild to severe disease stages, average disease duration was 4.9 years and age at onset was 62.6).…”
Section: Depressionmentioning
confidence: 99%
“…Subsequent investigations noted decreased fractional anisotropy values bilaterally in the mediodorsal thalamus correlating with increasing depression severity in Parkinson's disease patients, as assessed by the Hamilton Depression Scale. This suggests decreased viability of neurons or white matter fibers projecting to or from the mediodorsal thalamus [11]. A more recent DTI study, examining only the uncinate fasciculus as a region of interest, was unable to find a difference between depressed and nondepressed Parkinson's disease groups, in terms of fractional anisotropy values.…”
Section: Depression and Apathymentioning
confidence: 93%